Reflection of Child Protection on the Settlement of Child Sexual Violence In Indonesia: An Analysis of Court Decisions in 2019-2020 - Rusmilawati Windari; Istianah Za; Souad Ezzerouali (Trunojoyo Madura University, 2025)
Protection of children from sexual violence is a shared responsibility of all parties, including the judiciary. One of the efforts to protect children by the judiciary is manifested in court decisions on cases of sexual violence against children. As a form of law enforcement in concreto, the study of this court decision will provide a signal for criminal law reform related to the regulation of sexual violence against children in Indonesia. This article aims to examine the reflection of child protection in the resolution of cases of sexual violence against children in Indonesia in 2019-2020. As normative research, a single issue is studied using a statutory, conceptual, and case approach and then analyzed using the descriptive qualitative method. A comprehensive synthesis of statutory analysis, doctrinal interpretation, and systematic case examination was concluded. The discussion shows that the majority of settlements of sexual violence cases against children have reflected the protection of children. However, 3 three limitations signaled criminal law reform: the absence of criminal law guidelines, the lack of specifically formulated minimum fines, and the absence of sanctions for victim-oriented treatment.